Association of outdoor light at night with obstructive sleep apnoea: A cross-sectional study among adults in Southern China - Suhan WANG; Gongbo CHEN; Yan CHEN; Hailin XIONG; Qiong OU (环境与职业医学)
BackgroundObstructive sleep apnea (OSA) is a sleep disorder characterized by recurrent episodes of obstruction of the upper airway during sleep. Given the substantial number of OSA patients, it is urgently in need to address the burden on society. Current available evidence linking outdoor light at night (LAN) to OSA is scarce. ObjectiveTo explore the relationships regarding outdoor LAN and OSA among residents in Southern China. MethodsA total of 3925 hospitalized patients in Guangdong Provincial People's Hospital Sleep Center were recruited between January 1, 2005 and December 31, 2015. The severity of OSA was determined by apnea-hypopnea index (AHI) using polysomnography or home sleep test. The annual Suomi National Polar-orbiting Partnership Visible Infrared Imaging Radiometer Suite (NPP-VIIRS)-like LAN data with a 500 m spatial resolution were used to evaluate outdoor LAN levels of the participants 1, 3, and 5 years before undergoing sleep monitoring. Generalized linear regression models were utilized to examine the associations of outdoor LAN with OSA. ResultsThe ORs (95%CIs) of OSA, mild OSA, and moderate OSA were 1.175 (1.021, 1.351), 1.215 (1.038, 1.421), and 1.195 (1.003, 1.425) respectively for per interquartile range (IQR) increment in three-year average outdoor LAN. The results of stratified analyses showed a higher OR of 1.933 (95%CI: 1.424, 2.637) in female than male participants (P interaction < 0.001). Additionally, the ORs of OSA did not substantially change using one-year/ five-year instead of three-year average outdoor LAN. ConclusionOur findings demonstrate that an elevated outdoor LAN is significantly associated with higher odds of OSA (especially mild and moderate OSA) in Southern China, especially in females. An effective outdoor LAN management and policy-making framework has been suggested as potential preventive measures to reduce burden of OSA.